A Family of Lector-Priests at Edfu: Oriental Institute Stela E11455 and the 'Ib Family during the Early Eighteenth Dynasty - Bandy, Kathryn E..
This article presents the study of two stelae from Edfu dating to the early Eighteenth Dynasty that represent members of the same extended family of lector-priests from Edfu (Oriental Institute E11455 and Princeton Y1993-151). The texts of both stelae were published in the early twentieth century; however, neither stela has been comprehensively published. The two stelae present the opportunity to revisit the family’s genealogy and chronological position. The study also considers dating criteria for late Second Intermediate period and early Eighteenth Dynasty stelae and assesses the contemporary positioning and role of lector-priests. Finally, it briefly addresses the influence of documentary scribal culture on monumental inscriptions vis-a?-vis the late Second Intermediate period–early New Kingdom Tell Edfu Ostraca. doi: http://dx.doi.org/10.5913/jarce.56.2020.a004